Parental Education and Children’s Schooling Outcomes : Is the Effect Nature, Nurture, or Both? Evidence from Recomposed Families in Rwanda - de Walque, Damien (World Bank, Washington, DC, 2012)
Educated parents tend to have educated children. But is intergenerational transmission of human capital more nature, more nurture, or both? The author uses household survey data from Rwanda that contains a large proportion of children living in households without their biological parents. The data allows him to separate genetic from environmental parental influences. The nonrandom placement of children is controlled by including the educational attainment of the absent biological parents and the type of relationship that links the children to their "adoptive" families. The results of the analysis suggest that the nurture component of the intergenerational transmission of human capital is important for both parents, contrary to recent evidence proposed by Behrman and Rosenzweig (2002) and Plug (2004). The author concludes that mothers education had no environmental impact on children s schooling. Interestingly, mothers education matters more for girls, while fathers education is more important for boys. Finally, an important policy recommendation in the African context emerges from the analysis: the risk for orphans or abandoned children to lose ground in their schooling achievements is minimized if they are placed with relatives.